Applicability of the surgical site infection risk index to patients undergoing cardiac, neurologic and orthopedic surgery - Bonmann, Débora Marie da Silva; Lovatto, Carem Gorniak; Deutschendorf, Caroline (Clinical and Biomedical Research, 2017)
Introduction: The surgical site infection risk index (SSIRI) includes three risk factors for surgical site infection (SSI): potential for surgical contamination, duration of surgery, and patient’s ASA score. A patient having a preoperative American Society of Anesthesiologists (ASA) score of III, IV or IV; a surgery classified as either contaminated or dirty-infected; an operation with duration of surgery more than T hours, where T depends on the surgical procedure being performed are considered in risk of SSI. The SSIRI can be used as a method of postoperative surveillance. The aim of this study is to analyze the applicability of the SSIRI to patients undergoing cardiac, neurologic and orthopedic surgery. Methods: A retrospective cohort study including patients undergoing cardiac, neurological and orthopedic surgeries considered major, from January to December 2014, evaluated through review of medical charts of patients admitted to a university hospital in southern Brazil. Values of p <0.05 were considered significant. Results: A total of 761 patients were included in the study; of these, 122 (16%) developed SSI. The SSIRI did not demonstrate statistical significance to distinguish the patients most likely to develop SSI between the four levels of the ASA score. Black and brown patients, patients who underwent intraoperative blood transfusion, and patients who underwent surgical reintervention were more susceptible to SSI. Conclusions: The SSIRI could not be used as a method of postoperative surveillance for patients in the present study. The other risk factors found may serve as a guide to articulate SSI prevention strategies and, thus, minimize chances of development of serious infections. Keywords: Postoperative complications; infection; risk index